Analysis of Errors in the Use of the Enhanced Spelling System in the Undergraduate Theses of 2020 Cohort PJKR Students at Tadulako University - Raihan Mufli; Ida Nur'aeni; Asrianti; Ulfah; Andi Bismawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
In academic writing, spelling accuracy plays a crucial role as it directly impacts the clarity of ideas, text readability, and the quality of information delivery. Repeated spelling errors can hinder the effective communication of the writing's content to the reader. This study aims to describe the types of spelling errors found in the undergraduate theses of students from the Physical Education, Health, and Recreation Study Program (Class of 2020) at Tadulako University. A qualitative approach with a descriptive method was employed. Data were sourced from the students' theses, specifically focusing on Chapter 1 (Background). Data collection involved documentation, observation, and note-taking techniques. Data analysis utilized the Miles and Huberman model, comprising data reduction, data display, and conclusion drawing. The results indicate that the most frequent errors occurred in letter usage 72 instances, specifically involving capital letters 60 and italics 12. Additionally, there were 52 errors related to word writing, covering base words 28, derivative words or affixes 10, prepositions 8, and numerals/numbers 6. Punctuation errors totaled 31, specifically involving periods 6, commas 19, and hyphens 6. Five errors regarding loanwords were also identified. The findings suggest that the understanding and application of spelling rules in students' academic writing require more intensive attention.